PENERAPAN PEMBELAJARAN BERDIFERENSIASI MELALUI MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN IPAS KELAS 4 SD NEGERI 27 PALEMBANG - Syarifuddin; Sani Safitri; Rudi Hermawan; Turi Ashari; Yeni Permata Sari; Walliyu Friska Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to measure the effectiveness of implementing differentiated learning through the Project Based Learning model in improving learning outcomes of grade 4 primary school students in IPAS subjects. The importance of this research lies in the need to enhance learning outcomes through a more personalized and relevant approach. Applying the Project Based Learning model with differentiated learning is seen as important because it can maximize the potential of each learner. The novelty of this research is integrating differentiated learning with the Project Based Learning model which is rarely applied simultaneously in the primary school environment. Another novelty lies in how this approach not only targets improved learning outcomes, but also increases learner motivation and engagement through projects relevant to real life. This method provides a more meaningful and in-depth learning experience than traditional approaches that tend to be uniform. This research used an experimental method with a quasi-experimental approach. The research subjects were 4th-grade students of SD Negeri 27 Palembang. The class was divided into two groups, namely the experimental group using the Project Based Learning model with differentiated learning, and the control group using traditional learning methods. Learning outcome data was collected through pre-test and post-test while learning motivation data was collected through questionnaires. The mandatory outputs targeted in this research are scientific publication in Sinta 2 Accredited National Journal, Thesis, and reference book of IPAS material.